A Rationalized Review on Eradication of Covid-19 - Targeted Herbal Products - Dr. V. Sathyanathan,; Dr. S. K. Devipriya, (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Coronavirus disease 2019 (COVID-19) is a recurrent, quickly evolving disease outbreak caused by Coronavirus - 2 Severe Acute Respiratory Syndrome (SARS-CoV2). As of now (December 23, 2020), the cumulative number of known positive cases has been registered to be 78,481,916 in all affected countries around the world and the death toll is 1,726,632. There is no clear therapy to heal COVID-19 at present. No medicines have been developed so far, but people are making tremendous efforts to produce new therapies to disrupt COVID-19. Natural products have been playing an important role in the occurrence of diseases since ancient times. These products can be used as models for developing novel antimicrobial agents with diverse modes of action, as well as opening the door for the study of successful anti-COVID-19 antiviral drugs. The fundamental structure, infection and pathogenesis of the human SARS-CoV2 virus are identified with a focus on this. Due to the structure of these viruses, different natural products or plant extracts/bioactive compounds tested against SARS and MERS coronaviruses are also identified, and SARS-CoV2 may be used to design fresh anti-virus drugs. The antiviral activity against SARS-CoV2 viruses in natural products with the ability to combat SARS, MERS and other viruses illustrated in this article can be specifically used for more preclinical research. Therefore, to save the lives of many people around the world, all efforts should be focused on addressing this serious issue.